Legal Political on Worker Protection in The Provision of Religious Holiday Allowances - Nurikah Nurikah; H.E Rakhmat Jajuli; Muhammad Rizki (Al-Mustashfa: Jurnal Penelitian Hukum Ekonomi Syariah, 2025)
The Religious Holiday Allowance (THR) represents a normative right that employers are legally obligated to fulfill as part of fair labor practices. Nevertheless, violations and legal ambiguities persist, particularly following the enactment of Law Number 11 of 2020 on Job Creation, which altered the structure of labor protection in Indonesia. This study employs a doctrinal (normative juridical) research method, combining statutory and conceptual approaches, supported by a comparative analysis of Malaysia, Saudi Arabia, and the Netherlands to examine convergences and divergences in THR regulation. Data were drawn from primary, secondary, and tertiary legal materials and analyzed descriptively and analytically. The results show that Indonesian law, especially the Job Creation Law, does not explicitly regulate THR but delegates it to subordinate instruments such as Government Regulation No. 36 of 2021 and Ministerial Regulation No. 6 of 2016, resulting in weak legal protection and the absence of criminal sanctions for non-compliance. In contrast, Malaysia and Saudi Arabia apply policy-based holiday bonuses grounded in administrative and cultural frameworks, while the Netherlands integrates holiday pay into its statutory wage system (vakantiegeld), ensuring stronger legal certainty. The legal-political analysis highlights a continuing tension between worker protection and employer flexibility within Indonesia’s investment-oriented legal reforms. Strengthening THR governance through clearer statutory mandates and enforceable sanctions is essential to reaffirm THR as a constitutional right consistent with the 1945 Constitution and ILO standards.Keywords: legal politics; worker protection; religious holiday allowance; Job Creation Law; comparative law.